Peran Media Sosial dalam Meningkatkan Penjualan Jersey Custom Olahraga - Agnes Ias Septiana Manik; Britnay Hany Sitompul; Andreas Syabudiman Damanik; Nur Kholilah Harahap; Kevin Reynaldi Simanungkalit; Petrus Edwin Sinaga; Jonatan Purba (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of social media in boosting sales of custom sports jerseys. Advances in information and communication technology have encouraged businesses to utilize social media as an effective, efficient, and wide-reaching marketing tool. This study employs a quantitative approach using a survey method targeting consumers who have previously purchased custom jerseys via social media. Data collection was conducted through the distribution of questionnaires, while data analysis utilized descriptive and inferential statistics. The results indicate that social media has a significant influence on increasing sales of custom sports jerseys, particularly through visual promotion, consumer interaction, ease of access to information, and customer trust. Social media platforms such as Instagram, Facebook, and TikTok have proven capable of increasing consumer purchasing interest through engaging content and appropriate marketing strategies. Thus, the optimal utilization of social media can serve as an effective strategy for businesses to boost sales of custom sports jerseys.